A method for preparing magnetically responsive PBO film

By using PBO as the matrix material and adding magnetic particles, a high-strength, high-toughness and magnetic response characteristics PBO film was prepared, which solved the problem of insufficient application of existing magnetic response films under complex working conditions and significantly improved its Performance and reusability.

CN119060384BActive Publication Date: 2025-02-18SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411553816.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The matrix materials of existing magnetic responsive films, such as PDMS, have low strength, poor wear resistance, insufficient reusability, and have poor application under complex working conditions such as strong acid and alkali, high temperature, and high friction.

Method used

PBO film with magnetic responsive film is prepared by preparing PBO prepolymers of specific viscosity and adding micron-scale magnetic particles to it, and using high-temperature pressing to form a film, PBO film with magnetic responsive characteristics is prepared.

Benefits of technology

While maintaining excellent performance such as high strength and high toughness, PBO films can generate magnetic response and magnetodeform to external magnetic fields, significantly improving their application capabilities and reusability in complex working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060384B_ABST
    Figure CN119060384B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of intelligent response materials, and specifically relates to a method for preparing a magnetically responsive PBO film. The invention provides a method for preparing a PBO film that can generate magnetic responsiveness to an external magnetic field while maintaining high strength and high toughness. The PBO film not only has magnetic response characteristics, but also has excellent characteristics of PBO such as high strength, high toughness, high stability, corrosion resistance, fire resistance, friction resistance, and hydrophobicity. The film has broad application prospects in the field of adjustable films under complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of intelligent response materials, and in particular relates to a method for preparing a magnetic response PBO film. Background Art

[0002] Smart response materials refer to a new type of composite material that can sense environmental stimuli (including external stimuli such as light, temperature, electric field, magnetic field, etc.), analyze and judge them, and respond appropriately. They have become one of the most promising new materials in the 21st century and have broad application prospects in many fields such as microfluidic manipulation platforms, biochemical detection and analysis, and material filtration. Among them, magnetic response materials have gradually attracted more and more attention due to their many advantages such as instantaneous responsiveness, convenience, and safety, which is of great significance to the development of emerging smart materials.

[0003] As an important branch of magnetic responsive materials, magnetically responsive films (surfaces) are mainly used in the following areas: regulation of interfacial wetting and adhesion properties, microfluidic manipulation, magnetosensitive sensing technology, and magnetic control components. It is mainly made of viscoelastic materials as the matrix, and is prepared by filling micro-nano-level magnetically responsive particles inside. It not only exhibits the physical properties of the matrix, but also exhibits magnetic response properties due to the presence of magnetic particles. At present, the main material matrix reported for magnetically responsive films is viscoelastic materials such as PDMS. Such matrix materials have low strength and poor wear resistance, which leads to poor reusability of the film. In addition, the corrosion resistance and flame retardancy of such matrix materials are relatively insufficient. When faced with comprehensive and complex working conditions such as strong acid and alkali, high temperature, and high friction, its applicability is poor. PBO fiber is a high-strength, high-modulus synthetic fiber with excellent heat resistance, chemical resistance, and tensile and compressive properties. It is known as the "super fiber of the 21st century." Since PBO is not a viscoelastic material, and the research and development and production of PBO in China is still in the optimization stage, PBO has not been selected as a magnetically responsive matrix material in the existing technology. Therefore, applying PBO as a magnetically responsive matrix material is expected to improve the shortcomings of viscoelastic matrix materials, such as low strength, poor wear resistance, and poor reusability. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a magnetically responsive PBO film, which uses PBO as a magnetically responsive substrate to prepare a PBO film with magnetically responsive characteristics. While maintaining excellent properties such as high strength and high toughness, the PBO film can generate a magnetic response to an external magnetic field and undergo magnetoinduced deformation. It has a strong ability to cope with complex working conditions and environments, and has certain application prospects in the field of controllable films.

[0005] The present invention prepares a PBO prepolymer with a specific viscosity, mixes magnetic particles into the prepolymer, and then directly presses the PBO mixed slurry mixed with micron-sized magnetic particles into a film at a high temperature, thereby preparing a PBO film with magnetic response characteristics. While maintaining excellent properties such as high strength and high toughness, the PBO film can generate a magnetic response to an external magnetic field and undergo magneto-induced deformation, has a strong ability to cope with complex working conditions and environments, and has certain application prospects in the field of adjustable films.

[0006] In the existing PBO preparation process, the polymerization reaction for preparing PBO is carried out in polyphosphoric acid. After the polymerization is completed, a PBO / PPA lyotropic liquid crystal solution system with extremely high viscosity is formed. The concentration of PBO is high enough to ensure the good mechanical properties of the film after hot pressing and eliminate the need for subsequent dephosphorylation post-treatment. For PBO / PPA slurry, in the absence of external force, when the temperature is low, this system has almost no fluidity; when the temperature is higher than 100°C, the viscosity of the PBO / PPA slurry is significantly reduced and gradually becomes thinner. Therefore, after the PBO polymerization reaction is completed, it appears in a slurry state at high temperature. At this time, by adding micron-sized magnetic particles and stirring evenly, the magnetic particles can be evenly distributed in the slurry, and a PBO / PPA mixed slurry with micron-sized magnetic particles evenly mixed can be obtained.

[0007] On this basis, the present invention uses a flat hot press to directly press the mixed slurry (liquid crystal solution) obtained by polymerization into a film at a certain temperature, and solidifies the magnetic particles in the film while obtaining the film shape. Because in the obtained PBO / PPA slurry, the concentration of PBO is high enough to ensure the mechanical properties of the PBO film, while eliminating the post-treatment process of PPA separation; and because the viscosity of the PBO / PPA mixed slurry is significantly reduced when the temperature is higher than 100°C, the hot pressing temperature needs to be controlled above 100°C. Due to the unique high strength, high toughness, high stability, corrosion resistance, fire resistance and other excellent properties of PBO, the obtained magnetic responsive PBO film can still maintain excellent working stability under complex working environments.

[0008] Based on the above inventive concept, the method for preparing a magnetically responsive PBO film provided by the present invention specifically comprises the following steps:

[0009] (1) Adding magnetic particles: adding magnetic iron powder particles to the PBO prepolymer, maintaining the temperature at 150-160° C., introducing inert gas nitrogen, and mixing and stirring to obtain a mixed prepolymer with magnetic particles evenly distributed therein; the magnetic iron powder particles account for 33-60 wt % of the mixed prepolymer;

[0010] PBO prepolymer is sensitive to temperature, has high viscosity at low temperature and is easily oxidized at high temperature. The mixed prepolymer prepared by the above method has good fluidity and low viscosity, which is conducive to the stirring and uniform mixing of the prepolymer.

[0011] (2) Post-polymerization

[0012] The mixed prepolymer is further post-polymerized through a twin-screw extruder to finally obtain a PBO mixed slurry.

[0013] (3) Filtering

[0014] The PBO mixed slurry enters the melt filter for filtration to obtain a purer PBO mixed slurry.

[0015] (4) Hot pressing film forming

[0016] The filtered PBO mixed slurry is taken out and hot-pressed while still hot to obtain the magnetically responsive PBO film.

[0017] Preferably, in step (1), the particle size of the magnetic iron powder particles is 1-10 μm; the magnetic iron powder particles include various forms of Fe-containing particles, which are interchangeable, as long as their components contain iron, have a particle size of 1-10 μm, and are magnetic. Too high a concentration of magnetic particles will affect film formation, or may have an adverse effect on the strength of the film after formation; too low a concentration will result in a magnetic response level that cannot meet the requirements. Preferably, the proportion of magnetic iron powder particles in the above-mentioned mixed prepolymer is 50wt%.

[0018] In addition, other magnetic micron-sized particles may be used to replace the magnetic iron powder particles. However, based on cost considerations, the above-mentioned magnetic iron powder particles are preferably used.

[0019] Preferably, the viscosity of the PBO prepolymer in step (1) is 100-200 Pa·s.

[0020] Furthermore, the preparation method of the PBO prepolymer in step (1) is as follows:

[0021] 1) Mixing and degassing: The solid powder of polyphosphoric acid, 4,6-diaminoresorcinol hydrochloride, terephthalic acid, phosphorus pentoxide and antioxidant stannous chloride are put into the reactor and stirred at low temperature to disperse evenly, and mixed and degassed. The mixed degassing process is to evacuate the mixed materials at a certain temperature;

[0022] 2) Prepolymerization: After the mixed degassing is completed, inert gas nitrogen is introduced into the reactor, and the reactor is heated to 90-100°C for 2-4h, 110-120°C for 2-4h, 125-135°C for 3-5h, and 150-160°C for 2-7h. When the temperature is raised to 110-120°C and 125-135°C, phosphorus pentoxide is added once respectively, and PBO prepolymer can be obtained through prepolymerization reaction;

[0023] The PBO polymerization reaction is an exothermic reaction, and the temperature rises through the temperature stage reaction. At the same time, the reaction needs to be kept warm and prevented from heat dissipation.

[0024] Preferably, in step 1), the mass of 4,6-diaminoresorcinol hydrochloride accounts for 13-23wt% of the mass of the PBO prepolymer, the total mass of phosphorus pentoxide input accounts for 21.4-26.7wt% of the mass of the PBO prepolymer, the mass of stannous chloride accounts for 0.2-1.5wt% of the mass of the PBO prepolymer, and the molar ratio of terephthalic acid input to 4,6-diaminoresorcinol hydrochloride is (1-1.05:1); the remainder in the PBO prepolymer is polyphosphoric acid.

[0025] The particle size of terephthalic acid reaches 2-13μm, and the polyphosphoric acid is frozen at -50 to -30℃. After the frozen polyphosphoric acid is crushed, the particle size reaches 50-90μm; the mixed degassing process is to evacuate the mixed material at 80-90℃, the vacuum degree is -0.06 to -0.096MPa, and the mixed degassing time is 5-10h.

[0026] Preferably, in steps 1) and 2), the mass of phosphorus pentoxide initially added: the mass of phosphorus pentoxide added when the temperature rises to 110-120° C.: the mass of phosphorus pentoxide added when the temperature rises to 125-135° C. is 70-85:10-20:5-10. This addition method is adopted because phosphorus pentoxide absorbs water and releases heat. If all is added at the beginning, it will cause excessive heat release from the water generated by the absorption reaction, making it difficult to control the temperature, and will also cause excessive viscosity in the initial stage of the reaction, which is not conducive to stirring and dispersion.

[0027] Preferably, in step (2), the residence time of the material in the extruder is 70-120 min; the twin-screw extruder temperature zone has a total of 9 zones, and the temperature setting starts from the direction of the feed port and presents a step-by-step increasing trend: the first zone is 150-160°C, the second and third zones are 160-175°C, the fourth to sixth zones are 175-195°C, and the seventh to ninth zones are 195-225°C.

[0028] The above temperature control can further reduce the viscosity of the prepolymer, which helps to stir the magnetic particles evenly and avoids direct oxidation of the polymer.

[0029] Preferably, in step (3), the filter pore diameter of the melt filter is 40 μm.

[0030] Preferably, in step (4), the conditions for hot pressing film formation are: the temperature is set at 160-170°C, the working pressure is set at 34-36MPa, and the hot pressing time is maintained for 10-15 minutes. Too high or too low temperature is not conducive to film formation, so the above film forming temperature range is selected.

[0031] The preparation method of the magnetic responsive PBO film provided by the present invention uses PBO polymer as a matrix material, and after the magnetic particles are evenly distributed in the PBO polymer by physical doping, stirring and mixing, directly hot pressing to form a film, the yield is high and stable, and the method is simple and easy to operate; PBO is used as a magnetic responsive substrate to replace the previously commonly used PDMS-type colloid material, which greatly improves the ability of the magnetic responsive film to cope with comprehensive and complex working conditions such as strong acid and alkali, high temperature, and high friction. The obtained magnetic responsive PBO film maintains excellent properties such as high strength and high toughness, and has strong tensile damage resistance and wear resistance and strong deformation ability, and can generate magnetic response to the external magnetic field and undergo magnetoinduced deformation; at the same time, based on the performance of PBO, the PBO film also has a strong ability to cope with complex working conditions and environments, and has certain application prospects in the field of adjustable films, and specific examples are but not limited to:

[0032] 1) Regulate the surface properties of the film, such as wettability and adhesion, and achieve adhesion and desorption through magnetic field control switches and bionic structures; 2) Magnetic field regulates the deformation of the film to produce cavity adsorption force and prepare bionic suction cups; 3) Deformation is used to generate sensing, which can be used to prepare sensors and generate magnetic signal changes on the sensors to achieve the purpose of sensing; 4) Using alternating magnetic fields to make the film produce alternating deformations, which can be used as the driving force for the movement of bionic robots.

[0033] The magnetic responsive film proposed in the present invention, when applied to the above-mentioned fields, has significantly improved reusability and strength, thereby increasing its service life; in addition, the film's acid and alkali resistance is also significantly improved. Devices using the magnetic responsive film provided by the present invention can operate in acidic and alkaline environments and high-temperature liquid environments, such as bionic jellyfish motion robots. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the maximum magnetically induced elastic deformation degree of the magnetically responsive PBO film with different magnetic particle concentrations in Examples 1-3;

[0035] Figure 2 Comparison of the number of repeated deformations of the PDMS film in Comparative Example 1-3 and the PBO film in Example 1-3;

[0036] Figure 3The magneto-induced deformation degree of the magnetically responsive PBO film at three ratios of Examples 1-3. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the embodiments, which can enable those skilled in the art to more fully understand the present invention, but does not limit the present invention in any way.

[0038] Example 1 A method for preparing a magnetically responsive PBO film comprises the following steps:

[0039] (1) Mixing and degassing: The air in the reactor was replaced with nitrogen, and 434 g of 4,6-diaminoresorcinol hydrochloride, 338 g of terephthalic acid with a particle size of 8 μm, 1767 g of frozen polyphosphoric acid powder, 509.5 g of phosphorus pentoxide and 17.7 g of stannous chloride were mixed and put into the reactor. The reactor was heated to 85°C, and then vacuum was evacuated for degassing, with a vacuum degree of -0.095 MPa and a degassing time of 9 h.

[0040] (2) Prepolymerization: nitrogen was introduced into the reactor to change the negative pressure into a positive pressure of 0.01 MPa, and then the prepolymerization was continued. The material degassed in step (1) was heated to 100°C and kept warm for 4 h, then heated to 120°C, 145 g of phosphorus pentoxide was added and kept warm for 4 h, then heated to 135°C, 73 g of phosphorus pentoxide was added and kept warm for 5 h, and finally heated to 155°C and kept warm. During the prepolymerization, an apparent viscosity detector detected the viscosity of the material in real time. During the insulation at 155°C, it was detected that the apparent viscosity of the prepolymer material reached 200 Pa·s, and the prepolymerization reaction was terminated.

[0041] (3) Adding magnetic particles: Continue to add magnetic iron powder particles with a particle size of 1 μm to the prepolymer in the reactor (mass of magnetic iron powder particles: mass of PBO prepolymer = 1:2), maintain the temperature at 155°C, introduce inert gas nitrogen, and obtain a mixed prepolymer with evenly distributed magnetic particles through mixing and stirring.

[0042] (4) Post-polymerization: The mixed prepolymer material is transported into the twin-screw extruder for post-polymerization, and the material stays in the extruder for 90 minutes. The temperature zones of the twin-screw extruder are set from the feed inlet direction, the first zone: 155°C, the second and third zones: 175°C, the fourth to sixth zones: 190°C, the seventh to ninth zones: 220°C.

[0043] (5) Filtration: After the mixed material has completed the polymerization reaction in the extruder, it enters a melt filter with a filter element pore diameter of 40 μm for filtration to remove impurities such as bubbles, making the obtained mixed polymer slurry more conducive to film forming.

[0044] (6) Hot-pressing film formation: Take out about 25g of polymer mixed slurry with evenly distributed magnetic particles, and immediately place it between two polytetrafluoroethylene plates with a diameter of 10cm (for easy demoulding), and then place them together between two flat iron blocks, stack them flat and place them on a flat vulcanizer, the upper and lower plates of which have been heated to 160℃. Then, pressurize the flat vulcanizer to 35MPa, maintain for 10 minutes, and then remove the pressure to obtain a magnetically responsive PBO film with a thickness of 200 microns.

[0045] Example 2 A method for preparing a magnetically responsive PBO film comprises the following steps:

[0046] The PBO prepolymer prepared by (1) and (2) in Example 1 was used.

[0047] (3) Adding magnetic particles: Continue to add magnetic iron powder particles with a particle size of 1 μm to the prepolymer in the reactor (mass of magnetic iron powder particles: mass of PBO prepolymer = 1:1), maintain the temperature at 155°C, introduce inert gas nitrogen, and obtain a mixed prepolymer with evenly distributed magnetic particles through mixing and stirring.

[0048] (4) Post-polymerization: The mixed prepolymer material is transported into the twin-screw extruder for post-polymerization, and the material stays in the extruder for 90 minutes. The temperature zones of the twin-screw extruder are set from the feed inlet direction, the first zone: 155°C, the second and third zones: 175°C, the fourth to sixth zones: 190°C, the seventh to ninth zones: 220°C.

[0049] (5) Filtration: After the mixed material has completed the polymerization reaction in the extruder, it enters a melt filter with a filter element pore diameter of 40 μm for filtration to remove impurities such as bubbles, making the obtained mixed polymer slurry more conducive to film forming.

[0050] (6) Hot-pressing film formation: Take out about 25g of polymer mixed slurry with evenly distributed magnetic particles, and immediately place it between two polytetrafluoroethylene plates with a diameter of 10cm (for easy demolding), and then place them together between two flat iron blocks, stack them flat and place them on a flat vulcanizer, the upper and lower plates of which have been heated to 160℃. Then, pressurize the flat vulcanizer to 35MPa, keep it for 10 minutes, and then remove the pressure to obtain a magnetically responsive PBO film with a thickness of 200μm.

[0051] Example 3 A method for preparing a magnetically responsive PBO film comprises the following steps:

[0052] The PBO prepolymer prepared by (1) and (2) in Example 1 was used.

[0053] (3) Adding magnetic particles: Continue to add magnetic iron powder particles with a particle size of 1 μm to the prepolymer in the reactor (magnetic iron powder particles: PBO prepolymer mass = 3:2), maintain the temperature at 155°C, introduce inert gas nitrogen, and obtain a mixed prepolymer with evenly distributed magnetic particles through mixing and stirring.

[0054] (4) Post-polymerization: The mixed prepolymer material is transported into the twin-screw extruder for post-polymerization, and the material stays in the extruder for 90 minutes. The temperature zones of the twin-screw extruder are set from the feed inlet direction, the first zone: 155°C, the second and third zones: 175°C, the fourth to sixth zones: 190°C, the seventh to ninth zones: 220°C.

[0055] (5) Filtration: After the mixed material has completed the polymerization reaction in the extruder, it enters a melt filter with a filter element pore diameter of 40 μm for filtration to remove impurities such as bubbles, making the obtained mixed polymer slurry more conducive to film forming.

[0056] (6) Hot-pressing film formation: Take out about 25g of polymer mixed slurry with evenly distributed magnetic particles, and immediately place it between two polytetrafluoroethylene plates with a diameter of 10cm (for easy demolding), and then place them together between two flat iron blocks, stack them flat and place them on a flat vulcanizer, the upper and lower plates of which have been heated to 160℃. Then, pressurize the flat vulcanizer to 35MPa, keep it for 10 minutes, and then remove the pressure to obtain a magnetically responsive PBO film with a thickness of 200μm.

[0057] Comparative Example 1

[0058] A PDMS film, the preparation method thereof has the following steps:

[0059] (1) Use a high-precision balance to measure the PDMS precursor and curing agent in a mass ratio of 10:1, put them into a beaker for mixing, and then use a glass rod to stir them in one direction. Then add magnetic particles according to the weight ratio of magnetic particles to PDMS precursor and curing agent of 1:2 and stir evenly. Put the beaker into a vacuum freeze dryer for vacuuming. After the air pressure in the dryer box is evacuated to less than 40 Pa, continue to maintain it for 3 minutes until a large number of bubbles generated during the stirring process are removed and there are no bubbles in the mixture.

[0060] The PDMS precursor and curing agent system are selected from Dow Corning SYLGARD184; the magnetic particles are the magnetic iron powder particles in Example 1.

[0061] (2) After the vacuuming is completed, take the beaker out of the dryer and pour the PDMS mixture in the beaker into the mold processed by 3D printing (evenly apply a layer of vaseline in the groove to facilitate subsequent demolding). The amount poured should slightly overflow the groove, and then continue to place it in the vacuum dryer to repeat the vacuuming process in step (1).

[0062] (3) Take out the vacuumed mold, evenly apply a layer of Vaseline on the surface of the glass slide (for easy demolding), and cover it on top of the mold. Squeeze out the excess PDMS and fix it with a clamp to make the surface of the cured PDMS flat.

[0063] (4) After the treatment is completed, place the mold in a constant temperature heating box and heat and cure for 10-60 minutes at a heating temperature of 60 °C.

[0064] (5) After the heating and curing is completed, the mold is taken out, the clamp and the glass slide are removed, and the PDMS is demolded to obtain the PDMS film.

[0065] Comparative Example 2

[0066] The method for preparing the PDMS film is basically the same as that in Comparative Example 1, except that in step (1), the weight ratio of the magnetic particles to the PDMS precursor and the curing agent is 1:1.

[0067] Comparative Example 3

[0068] The method for preparing the PDMS film is basically the same as that in Comparative Example 1, except that in step (1), the weight ratio of the magnetic particles to the PDMS precursor and the curing agent is 2:3.

[0069] Experimental Example 1

[0070] The magnetically responsive films prepared in the above Examples 1-3 were cut into 30 mm × 30 mm pieces and tested for their maximum magnetically induced elastic deformation under the same magnetic field strength (1 T). The magnetically induced deformation degree was tested by clamping the film at both ends and keeping the film flat, then applying a uniform magnetic field in a vertical direction, and measuring the vertical distance from the lowest point in the middle of the film to the original horizontal line height. The results are as follows: Figure 1 As shown, it was found that within a certain range, the higher the concentration of magnetic particles, the stronger the response ability to the magnetic field, the greater the maximum magnetically induced elastic deformation, and the better the effects in terms of controllability and sensing.

[0071] The magnetically responsive films of Examples 1-3 were tested for their magnetostriction at different magnetic field intensities. The results are as follows: Figure 3 As shown in FIG. 1 , as the concentration of magnetic particles in the film increases, the degree of magneto-induced deformation of the film gradually increases. Also, as the magnetic field strength increases, the degree of magneto-induced deformation of the film also gradually increases.

[0072] Experimental Example 2

[0073] The number of repeated deformations of the PDMS films of Comparative Examples 1-3 and the PBO magnetically responsive films obtained in Examples 1-3 was detected. Specifically, the uniform magnetic field was repeatedly applied and removed to make the films continuously deform and recover the deformation until the films broke, and the maximum number of repeated deformations was recorded.

[0074] The results are as follows Figure 2 As shown in the figure, the PBO magnetic response film obtained in Examples 1-3 can be reused significantly more times than the PDMS film in Comparative Examples 1-3, and has stronger wear resistance and durability. Figure 2 It can be seen that with the increase of the concentration of magnetic particles in the magnetic responsive film, the durability of the film gradually decreases and the number of times it can be reused gradually decreases.

[0075] In summary, the present invention physically dopes magnetic responsive particles into PBO slurry and then presses it into a film at high temperature, so that the prepared PBO film not only has magnetic response characteristics, but also has excellent properties of PBO materials such as high strength, high toughness, high stability, corrosion resistance, fire resistance, friction resistance, hydrophobicity, etc. compared with the currently widely used base materials such as PDMS, which greatly improves the performance of the magnetic responsive film, making it more suitable for various complex working conditions such as strong acid and alkali, high friction, high repeatability, etc., and the scope of application is greatly increased.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a magnetically responsive PBO film, characterized in that: The following steps are involved: (1) Adding magnetic particles: adding magnetic iron powder particles to the PBO prepolymer, maintaining the temperature at 150-160° C., introducing inert gas nitrogen, and mixing and stirring to obtain a mixed prepolymer in which magnetic particles are evenly distributed; wherein the magnetic iron powder particles account for 33-60wt% of the mixed prepolymer; (2) Post-polymerization The mixed prepolymer is further post-polymerized through a twin-screw extruder to obtain a PBO mixed slurry; (3) Filtering The PBO mixed slurry enters the melt filter for filtration to obtain a purer PBO mixed slurry; (4) Hot pressing film forming The filtered PBO mixed slurry is taken out and hot-pressed while still hot to obtain the magnetically responsive PBO film.

2. The method for preparing a magnetically responsive PBO film according to claim 1, characterized in that: The particle size of the magnetic iron powder particles in step (1) is 1-10 μm; the viscosity of the PBO prepolymer in step (1) is 100-200 Pa·s, and the proportion of the magnetic iron powder particles in the mixed prepolymer is 50wt%.

3. The method for preparing a magnetically responsive PBO film according to claim 1, characterized in that: The preparation method of the PBO prepolymer in step (1) is as follows: 1) Mixing and degassing: The solid powder of polyphosphoric acid, 4,6-diaminoresorcinol hydrochloride, terephthalic acid, phosphorus pentoxide and antioxidant stannous chloride are put into the reactor and stirred at low temperature to disperse evenly, and mixed and degassed. The mixed degassing process is to evacuate the mixed materials at a certain temperature; 2) Prepolymerization: After the mixed degassing is completed, inert gas nitrogen is introduced into the reactor, and the reactor is heated to 90-100°C for 2-4h, 110-120°C for 2-4h, 125-135°C for 3-5h, and 150-160°C for 2-7h. Phosphorus pentoxide is added once in the reaction section of 110-120°C and 125-135°C respectively, and PBO prepolymer can be obtained through prepolymerization.

4. The method for preparing a magnetically responsive PBO film according to claim 3, characterized in that: In step 1), the mass of 4,6-diaminoresorcinol hydrochloride accounts for 13-23wt% of the mass of the PBO prepolymer, the total mass of phosphorus pentoxide input accounts for 21.4-26.7wt% of the mass of the PBO prepolymer, the mass of stannous chloride accounts for 0.2-1.5wt% of the mass of the PBO prepolymer, and the molar ratio of terephthalic acid input to 4,6-diaminoresorcinol hydrochloride is (1-1.05:1); the balance in the PBO prepolymer is polyphosphoric acid.

5. The method for preparing a magnetically responsive PBO film according to claim 3, characterized in that: The particle size of terephthalic acid reaches 2-13 μm, and the polyphosphoric acid is frozen at -50 to -30°C. After the frozen polyphosphoric acid is crushed, the particle size reaches 50-90 μm; the mixed degassing process is to evacuate the mixed material at 80-90°C, the vacuum degree is -0.06 to -0.096 MPa, and the mixed degassing time is 5-10 hours.

6. The method for preparing a magnetically responsive PBO film according to claim 3, characterized in that: In steps 1) and 2), the mass of phosphorus pentoxide initially input: the mass of phosphorus pentoxide input when the temperature is raised to 110-120°C: the mass of phosphorus pentoxide input when the temperature is raised to 125-135°C is 70-85:10-20:5-10.

7. The method for preparing a magnetically responsive PBO film according to claim 1, characterized in that: In step (2), the residence time of the material in the extruder is 70-120 min; the twin-screw extruder temperature zone has a total of 9 zones, and the temperature setting starts from the direction of the feed port and presents a step-by-step increasing trend: the first zone is 150-160°C, the second and third zones are 160-175°C, the fourth to sixth zones are 175-195°C, and the seventh to ninth zones are 195-225°C.

8. The method for preparing a magnetically responsive PBO film according to claim 1, characterized in that: The filter pore diameter of the melt filter in step (3) is 40 μm.

9. The method for preparing a magnetically responsive PBO film according to claim 1, characterized in that: The conditions for hot pressing film formation in step (4) are as follows: the temperature is set at 160-170° C., the working pressure is set at 34-36 MPa, and the hot pressing time is maintained for 10-15 minutes.

Citation Information

Patent Citations

  • Preparation method of poly(p-phenylene benzobisoxazole) fibers

    CN112760737A

  • Preparation method and application of magnetic stimulation response actuator based on magnetic anisotropy composite film

    CN118063816A